2007
DOI: 10.1111/j.1834-7819.2007.tb06138.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing oral health of adults with physical and intellectual disabilities in various living arrangements

Abstract: References 1. Parker DAS, Ong .l, Marino V, Kerr DlB. Gabapentin activates presynaptic GABA B hetero-receptors in rat cortical slices. Eur ] PharmacoI2004;495:137-143. 2. Nassery K, Marino V, Parker DAS. Uptake and release of [3HI GABA in human dental pulp. Arch Oral BioI 2007;52:607-613. 3.0ng ], Marino V, Parker DAS, Kerr DlB, Blythin DJ. The morpholino-acetic acid analogue Sch 50911 is a selective GABA B receptor antagonist in rat neocortical slices. Eur ] Pharmacol 1998;362:35-41.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 2 publications
1
10
1
Order By: Relevance
“…In contrast to the available literature, which reports a high prevalence of untreated dental caries, this study found the prevalence of untreated decay was only 16.9%, which was lower than the national estimates of 25.8% and 27.1% among people aged 15–34 years and 35–54 years (respectively) in the Australian population (12). The prevalence reported was much lower than the English studies (14, 15) which reported a prevalence of 58% among 25–44 years old people with intellectual disability and 61% among 25–34 years old handicapped adults, respectively. Also, the proportion of missing to filled teeth was not higher as reported by Cumella et al.…”
Section: Discussioncontrasting
confidence: 70%
“…In contrast to the available literature, which reports a high prevalence of untreated dental caries, this study found the prevalence of untreated decay was only 16.9%, which was lower than the national estimates of 25.8% and 27.1% among people aged 15–34 years and 35–54 years (respectively) in the Australian population (12). The prevalence reported was much lower than the English studies (14, 15) which reported a prevalence of 58% among 25–44 years old people with intellectual disability and 61% among 25–34 years old handicapped adults, respectively. Also, the proportion of missing to filled teeth was not higher as reported by Cumella et al.…”
Section: Discussioncontrasting
confidence: 70%
“…Many people with PID meet both of these criteria; 95 per cent of people with PID in South Australia receive a disability support pension, with 17 per cent of this sub-population experiencing untreated decay. 15 Problems exclusive to those living at family homes and community housing were transportation difficulties, especially for wheelchair bound care recipients, and inadequate disabled parking outside dental clinics, resulting in late arrivals for appointments. As services are provided within the institution, care recipients at institutions have no transportation and parking problems.…”
Section: Discussionmentioning
confidence: 99%
“…The data were weighted to represent the South Australian population of adults with disabilities. 6 Unweighted data were used to describe characteristics of carers and care recipients. Subsequent analyses were undertaken using weighted data.…”
Section: Resultsmentioning
confidence: 99%